"A Library Within a Library": Organizational Design as Perceived by Academic Government Information Librarians. Issue 1 (2nd January 2021) - Trujillo, Nicole; Tallman, Kathryn W.
Abstract: Government information librarians in academic libraries often serve multiple roles, providing public and technical services for government information along with other duties as assigned. This study conducted semi-structured interviews with 10 academic Federal Depository Library Program coordinators to better understand how they view the organizational design of their library. The study finds that coordinators are able to clearly identify their own priorities for government information. However, their ability to integrate these priorities with larger university and library goals depends on the presence of a strategic plan and a clear method by which to adapt priorities to a larger plan. The study also discusses themes of data services, physical collection legacies, and access and discovery of government information materials.